2021
DOI: 10.1002/cnma.202100082
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Assembly and Separation under UV‐Induced Convective Flows and on Inclines

Abstract: Achieving directed motility and separation of colloidal particles is a crucial requirement in a range of technological areas. Herein, we describe a system that exploits the photothermal properties of plasmonic nanoparticles for the assembly and separation of larger microparticles. Irradiating an aqueous suspension of gold or silver nanoparticles with UV light generates thermal convection which can be used to move and organize larger particles. Moving the UV light source allows the relocation of the particle cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Moreover, the convective fluid flow velocity is known to increase with the increasing height of the chamber. 28,29 Accordingly, we observed an increase in droplet velocity with the increasing height of the fluid in the chamber (Figure 2C).…”
Section: ■ Results and Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Moreover, the convective fluid flow velocity is known to increase with the increasing height of the chamber. 28,29 Accordingly, we observed an increase in droplet velocity with the increasing height of the fluid in the chamber (Figure 2C).…”
Section: ■ Results and Discussionmentioning
confidence: 65%
“…Thus, for both water and PFO, the droplet velocity increased with size. The size dependence of droplet velocities can be explained by the nature of the convective flow. , Because of the no-slip boundary conditions, the fluid velocity near the bottom of the chamber increased on moving upward from the substrate (Figure C). Hence, bigger droplets experience faster fluid flow because they stick out more into the fluid.…”
Section: Resultsmentioning
confidence: 99%
“…When these nanoparticles were irradiated at their plasmon resonance wavelength, they generated a temperature increase that led to notable fluid flow rates, reaching velocities up to 179 μm/s. Similarly, Kauffman et al 59 delved into how the photothermal properties of plasmonic nanoparticles could facilitate the movement and organization of larger microparticles via thermal convection. Both studies reported fluid velocities in the micrometers-per-second range, aligning closely with our observations.…”
Section: Numerical Validationmentioning
confidence: 99%